In lands of foreign currency credit, bank lending channels run through? The effects of monetary policy at home and abroad on the currency denomination of the supply of credit - Steven Ongena; Ibolya Schindele; Dzsamila Vonnák (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We analyze the differential impact of domestic and foreign monetary policy on the local supply of bank credit in domestic and foreign currencies. We analyze a novel, supervisory dataset from Hungary that records all bank lending to firms including its currency denomination. Accounting for time-varying firm-specific heterogeneity in loan demand, we find that a lower domestic interest rate expands the supply of credit in the domestic but not in the foreign currency. A lower foreign interest rate on the other hand expands lending by lowly versus highly capitalized banks relatively more in the foreign than in the domestic currency.
Keywords: E51; F3; G21; 330; Bank balance-sheet channel; monetary policy; foreign currency lending